Determinan Burnout syndrome pada Tenaga Kesehatan di Rumah Sakit - Nurhaeni Sikki; Dinda Dwi Anjani; Teringet Ginting; Bella Safitri; Aureliany Auli Rasyid; Muhammad Fatih Alabiyyu (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Burnout syndrome is one of the most common occupational health problems experienced by healthcare workers in hospitals. High service demands, excessive workloads, shift work, emotional stress related to patient care, and limited healthcare resources increase the risk of burnout among healthcare professionals. This condition adversely affects not only the physical and mental well-being of healthcare workers but also service quality, patient safety, organizational productivity, and the sustainability of healthcare systems. Although research on burnout has expanded significantly, previous studies have reported varying findings regarding the primary determinants contributing to burnout, highlighting the need for a comprehensive synthesis of scientific evidence. This study aimed to identify and analyze the determinants of burnout syndrome among healthcare workers in hospitals based on scientific evidence published between 2020 and 2026. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. The findings indicate that the determinants of burnout syndrome can be classified into three major categories: individual factors, organizational factors, and work environment factors. High workload, shortage of healthcare personnel, long working hours, shift work, role conflict, inadequate organizational support, ineffective leadership, and poor work–life balance were identified as the most consistently reported determinants. Burnout was also associated with an increased risk of medical errors, reduced quality of healthcare services, lower job satisfaction, higher turnover intention, and compromised patient safety. The review concludes that burnout syndrome among healthcare workers is a multidimensional issue influenced by the interaction of individual, organizational, and workplace factors. Therefore, effective prevention strategies should adopt a comprehensive organizational approach, including workload management, strengthening organizational support, leadership development, provision of mental health services, and implementation of healthcare worker well-being programs.